Christmas story (The): with Ruth Morehead's Holly Babes. (New York : Random House, 1986)
A simple retelling of the Christmas story according to the Gospels of St. Matthew and St. Luke, set up as a Christmas pageant with Ruth J. Moreheads's Holly Babes acting the parts.
Keywords: Jesus Christ--Nativity; Bible stories--N.T.